Gelatin nanocomposite films incorporated with magnetic iron oxide nanoparticles for shelf life extension of grapes. Issue 4 (11th May 2020) - Mehmood, Zaffar; Sadiq, Muhammad Bilal; Khan, Muhammad Rehan
Abstract: Nanocomposite films were obtained by solution casting method from aqueous solution of bovine gelatin with addition of various concentrations of magnetic iron oxide (MIO) nanoparticles (NPs) (5, 10, 15, and 20% w/w of dry gelatin). The incorporation of MIO NPs improved the mechanical and physical properties of the nanocomposites. The increase in concentration of NPs up to 10% improved barrier and mechanical properties which slightly decreased after increasing the concentration beyond that limit due to particle agglomeration. The scanning electron microscopy and X‐ray diffraction (XRD) were used to evaluate the morphology and crystalline structure of gelatin nanocomposite films, respectively. Gelatin nanocomposites with 20% w/w NPs exhibited the highest antimicrobial activity against Escherichia coli (7.1 ± 0.085 mm) and Staphylococcus aureus (8.22 ± 1.04 mm). Finally, the potential of gelatin/MIO nanocomposites as packaging material was evaluated to extend the shelf life of grapes. The gelatin/MIO nanocomposites can be used as a replacement to non‐biodegradable packaging. Abstract : Nanocomposite films of gelatin/magnetic iron oxide (MIO) NPs were prepared with improved physical, mechanical, and barrier properties. The potential of gelatin/MIO nanocomposites as packaging material was evaluated to extend the shelf life of grapes. Thus, gelatin/MIO nanocomposites can be used as replacement to non‐biodegradable packaging.